Strategy in talent systems: Top-down and bottom-up approaches - Taylor, J.; Macnamara, A.; Taylor, R. D. (Frontiers in Sports and Active Living, 2022)
Building on a large volume of recent research in talent identification and development, this paper future directions for research and practice. We suggest that strategic coherence become a greater point of emphasis in both, with the Performance, Outcome and Process framework holding the potential to signal various markers of effectiveness. Secondly, greater recognition of the need to deploy limited resources where they promote movement toward these markers of effectiveness. Finally, we make recommendations for the operationalising of strategy in talent and performance systems by considering the integration of top down and bottom-up strategic processes.